2016
DOI: 10.1634/theoncologist.2015-0356
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Localization of Human Equilibrative Nucleoside Transporter 1 in Tumor Cells May Predict Response to Adjuvant Gemcitabine in Resected Cholangiocarcinoma Patients

Abstract: Background. The use of gemcitabine as an adjuvant modality for cholangiocarcinoma (CC) is increasing, but limited data are available on predictive biomarkers of response. Human equilibrative nucleoside transporter 1 (hENT-1) is the major transporter involvedingemcitabineintracellularuptake.Thisstudyinvestigated the putative predictive role of hENT-1 localization in tumor cells of CC patients undergoing treatment with adjuvant gemcitabine. Methods. Seventy-one consecutive patients with resected CC receiving adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 26 publications
2
28
0
Order By: Relevance
“…Chemotherapy is well established for the first line with platinum-gemcitabine combination but not for the further lines [6,7] , though radical resection remains the only potentially curative treatment [8] . The role of adjuvant strategies in this pathology remains unclear [9][10][11] . Unfortunately, most patients present an advanced disease at the diagnosis and their prognosis is poor.…”
mentioning
confidence: 99%
“…Chemotherapy is well established for the first line with platinum-gemcitabine combination but not for the further lines [6,7] , though radical resection remains the only potentially curative treatment [8] . The role of adjuvant strategies in this pathology remains unclear [9][10][11] . Unfortunately, most patients present an advanced disease at the diagnosis and their prognosis is poor.…”
mentioning
confidence: 99%
“…118,119 Among these transporters, hENT1 is a major transporter involved in gemcitabine cellular uptake. 120 In fact, hENT1 has been reported as a vital predictive marker of tumor response to gemcitabine-based therapy. 32,121,122 Clinical data showed that cancer patients with a decreased tumor expression of hENT1 have a significantly lower survival rate after gemcitabine treatment than those with tumors that express a higher level of hENT1.…”
Section: Nucleoside Transportersmentioning
confidence: 99%
“…In the May 2016 issue of The Oncologist , Brandi et al [1] explored the expression and localization of human equilibrative nucleoside transporter 1 (hENT-1) in paraffin-embedded tissues from radically resected cholangiocarcinoma patients. They highlighted the prognostic role of this transporter and identified hENT-1 as a potential biomarker to predict outcome after adjuvant therapy with gemcitabine [1].…”
mentioning
confidence: 99%
“…They highlighted the prognostic role of this transporter and identified hENT-1 as a potential biomarker to predict outcome after adjuvant therapy with gemcitabine [1]. …”
mentioning
confidence: 99%